PANDANGAN JAMAAH TABLIGH TERHADAP POLITIK: STUDI DI KECAMATAN NANGGALO KOTA PADANG - Candra Candra; Zamzami Zamzami; Deky Sukma Indra (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to, understand, describe and analyze the perspectives / views of the Tablighi Jamaah Nanggalo District, Padang City on the simultaneous selection of the Governor and Deputy Governor of West Sumatra in 2015. This study uses a conceptual, historical and case approach. Based on previous research, the average Tablighi Jamaah has preached by instilling anti-political ideology. But another side shows that the growth rate of the number of pilgrims is always increasing. If this phenomenon continues to develop, it is assumed that it will have an effect on the continued decline in voter turnout. The results of this study indicate that the political perceptions of the Jamaah Tabligh in Nanggalo Subdistrict have been divided into two, some of which have been directly involved and some are still surviving, not active in politics. This is based on several factors such as the diversity of social backgrounds and the diversity of religious understandings.